High-strength shape memory polyester composite fiber and preparation method thereof
By introducing glass fiber modified polyamide into shape memory polyester, the problem of insufficient mechanical properties of shape memory polyester fibers is solved, the tensile strength and shape memory properties are significantly improved, and its application range in the textile field is expanded. And reduce production costs.
Patent Information
- Application Number
- CN202411801912.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-02-14
AI Technical Summary
The application of existing shape memory polyesters in the textile field is limited by the insufficient mechanical properties of their textile fibers, and it is necessary to improve the mechanical properties of the fibers to expand the scope of application.
By introducing glass fiber modified polyamide as the reinforcement phase, the compatibility and interface bonding force of the shape memory polyester matrix and the polyamide are improved, thereby improving the mechanical properties of the shape memory polyester.
It significantly improves the tensile strength of shape memory polyester, improves the shape fixation rate and shape recovery rate, so that the fiber can better maintain and restore its original shape after being subjected to stress, while reducing the preparation cost and having a high cost-effectiveness. .
Smart Images

Figure CN119432020A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polymer materials, and in particular to a high-strength shape memory polyester composite fiber and a preparation method thereof. Background Art
[0002] Shape memory polyester refers to polyester polymer materials with shape memory effect. Its shape memory effect is based on the special structure and phase transition characteristics of the molecular chain. Under certain conditions such as temperature and stress, the molecular chain can undergo reversible conformational changes or phase transitions, so that the material exhibits shape memory function. Shape memory polyester has the advantages of light weight, large deformation, and adjustable elastic modulus, and has shown high application value in aerospace, biomedicine, 4D printing, textiles and other fields.
[0003] Professor Yang Keke's team synthesized all-biobased shape memory copolyesters using dimethyl itaconate, dimethyl sebacate and 1,4-butanediol as raw materials, and used UV-assisted FDM technology to manufacture elbow protection devices, etc. This study not only gave the model excellent shape memory properties, but also improved the anisotropy of its mechanical properties, with shape fixation and shape recovery values exceeding 90%. Jiang Ruiqiao and others used thermal initiators to initiate free radical crosslinking of polycaprolactone, and combined with the synergistic effect of secondary curing of ultraviolet light surface to prepare a series of polycaprolactone shape memory materials with different amounts of photoinitiator addition. Studies have shown that compared with the thermal cross-linking system, the shape memory performance and mechanical properties of the material are significantly improved after the combination of ultraviolet light surface secondary curing. When the mass fraction of the photoinitiator is 3%, the shape memory performance of the material reaches a peak, and the shape fixation rate and shape recovery rate are increased from 93.0% and 91.4% to 99.5% and 99.8%, respectively. The tensile strength and elongation at break are also increased from 42.5MPa and 658.1% to 49.9MPa and 805.0%, respectively. Ayesha Kausar et al. studied polyester / fullerene, polyester / graphene and polyester / carbon nanotube shape memory nanocomposites and found that the addition of different nanofillers will have a significant effect on the performance of shape memory polyester. For example, the polylactic acid / fullerene system exhibits an electroactive shape memory effect with a recovery time of <10s; the thermoresponsive polyester nanocomposite material containing graphene nanofillers has a shape fixation rate of 90~99% and a shape recovery rate of up to 100%; the shape memory polyester containing carbon nanotubes can generate electrical drive at a voltage of 20~40V, with a shape recovery rate of 80~100%, a shape fixation rate of 80~90%, and a shape recovery time of 5~15s.
[0004] However, in the actual production and application of shape memory polyester in the textile field, its application scope is greatly limited due to its insufficient mechanical properties of textile fibers. Therefore, it is of great significance to carry out research on improving the mechanical properties of shape memory polyester fibers. Shape memory polyester is a general term for polymers obtained by polycondensation of polyols and polyacids. It is a class of engineering plastics with excellent performance and wide applications. It mainly includes linear thermoplastic resins such as polyethylene terephthalate, polybutylene terephthalate and polyarylate. Among them, polyethylene terephthalate, as a traditional linear thermoplastic resin, has good fiber-forming properties and shape memory properties, and has potential application value in the textile field. However, the tensile strength of polyethylene terephthalate fibers is only about 48MPa, and it is very easy to break during weaving and drawing. In order to improve the mechanical properties of shape memory polyester fibers and enable them to be widely used in the textile field, the preparation and development of high-strength shape memory polyester composite fibers is imperative. At present, there are two main methods for modifying shape memory polyester: one is to use chemical modification to change the molecular chain structure, and the other is to use physical modification to change the aggregation state of the molecules, but these two methods have no obvious effect on improving the mechanical properties. Summary of the invention
[0005] In order to solve the problems existing in the prior art, the present invention provides a high-strength shape memory polyester composite fiber and a preparation method thereof, which adopts glass fiber modified polyamide as a reinforcing phase to improve the compatibility and interfacial bonding strength between the shape memory polyester matrix and the polyamide, thereby achieving the purpose of improving the mechanical properties of the shape memory polyester.
[0006] To achieve the above object, the present invention provides the following technical solution: a modified polyamide-reinforced shape memory polyester, comprising: Shape memory polyester matrix: polyethylene terephthalate-1,4-cyclohexanedimethanol ester; Reinforcement phase: glass fiber modified polyamide; Among them, the mass ratio of shape memory polyester matrix to reinforcement phase is 25:1~7:3.
[0007] Furthermore, the preparation of the shape memory polyester matrix is specifically as follows: Terephthalic acid, ethylene glycol and 1,4-cyclohexanedimethanol are mixed in a molar ratio of 1:1.2:0.8 to obtain a mixture; The mixed material is extruded through an extruder, and the temperature of each zone of the extruder is set as follows: 240°C-250°C for zone 1, 250°C-260°C for zone 2, 260°C-270°C for zone 3, and a die head temperature of 255°C-265°C to obtain polyethylene terephthalate-1,4-cyclohexanedimethanol ester.
[0008] Further, the preparation method of glass fiber modified polyamide is as follows: The glass fiber is immersed in a silane coupling agent treatment liquid to obtain a pretreated glass fiber; The polyamide and the pretreated glass fiber are mixed and then extruded through an extruder to obtain the glass fiber modified polyamide.
[0009] Further, in the step of immersing the glass fiber in a silane coupling agent treatment solution to obtain pretreated glass fiber, specifically: The amount of the silane coupling agent is 0.5% to 2% of the mass of the glass fiber; The glass fiber is completely immersed in the silane coupling agent treatment solution and stirred at 50°C to 80°C for 1 to 3 hours. The glass fiber is taken out and dried to obtain the pretreated glass fiber.
[0010] Further, in the step of mixing the polyamide and the pretreated glass fiber and extruding the mixture through an extruder to obtain the glass fiber modified polyamide, specifically: The polyamide and the glass fiber are mixed in a mass ratio of 20:1 to 7:3, stirred for 3 to 5 minutes at a stirring speed of 400 r / min to 1000 r / min to obtain a mixed material, and the mixed material is added to an extruder.
[0011] Further, in the step of mixing the polyamide and the pretreated glass fiber and extruding the mixture through an extruder to obtain the glass fiber modified polyamide, specifically: The temperature settings of each zone of the extruder are: zone 1 225℃~235℃, zone 2 235℃~245℃, zone 3 245℃~255℃, head temperature 230℃~250℃, and melt temperature 235℃~255℃.
[0012] Furthermore, polyethylene terephthalate-1,4-cyclohexanedimethanol ester and glass fiber modified polyamide are mixed in a mass ratio of 25:1 to 7:3, stirred for 5 min to 15 min at 500 r / min to 1000 r / min, and then extruded using an extruder.
[0013] Furthermore, the temperature of each zone of the extruder is set as follows: zone 1 240°C~250°C, zone 2 250°C~260°C, zone 3 260°C~270°C, and the die head temperature 255°C~265°C.
[0014] The present invention also provides a high-strength shape memory polyester composite fiber, which is prepared by melt spinning the modified polyamide-reinforced shape memory polyester, wherein the melt index of the modified polyamide-reinforced shape memory polyester is 32.0 g / 10 min to 45.0 g / 10 min.
[0015] Furthermore, during melt spinning, the temperature of each zone is set as: 210℃~220℃ for zone 1, 220℃~230℃ for zone 2, and 230℃~240℃ for zone 3; the temperature of the spinning box is controlled at 240℃~250℃; the screw extrusion pressure is 5MPa~10MPa, the spinning assembly pressure is 8MPa~12MPa, the screw speed is 30r / min~60r / min, and the spinning speed is 1000m / min~3000m / min.
[0016] The present invention also provides an application of a high-strength shape memory polyester composite fiber in composite fiber filling materials, textile and clothing fabrics, engineering materials, shoe materials, packaging materials or medical materials.
[0017] Compared with the prior art, the present invention has at least the following beneficial effects: The present invention provides a modified polyamide reinforced shape memory polyester, which effectively improves the compatibility and interfacial bonding force between the shape memory polyester matrix and the polyamide by introducing glass fiber modified polyamide as a reinforcing phase, thereby significantly improving the tensile strength of the shape memory polyester. The addition of modified polyamide not only improves the mechanical properties of the material, but also maintains the shape memory performance of the blended material. The polyamide phase provides better support and constraint for the shape memory polyester matrix, making the material more stable during the shape recovery process. The amide bond H atoms of the polyamide and the ester bond O atoms of the shape memory polyester combine to form hydrogen bonds under electrostatic action, thereby improving the interfacial bonding force between the two. This chemically bonded interface is less likely to phase separate when subjected to tension, thereby enhancing the overall performance of the composite material, and the glass fiber forms a structure similar to a "skeleton" in the polyamide matrix, which plays a role in supporting and bearing loads, further enhancing the mechanical properties of the material.
[0018] Furthermore, polyamide and glass fiber are both common industrial materials with large output and relatively low price. Compared with some high-performance shape memory materials, the preparation cost of the present invention is low, the production cycle is short, and it has a high cost performance.
[0019] The tensile strength of the composite fiber prepared by the modified polyamide-reinforced shape memory polyester of the present invention is significantly improved, which is more than 44% higher than the tensile strength of the shape memory polyester matrix, and the shape fixation rate and shape recovery rate are also improved, so that the fiber can better maintain and restore its original shape after being stressed. Because the addition of polyamide phase and glass fiber improves the thermal conductivity of the material, the temperature change of the material during heating and cooling is more uniform. This is conducive to the shape memory effect, so that the fiber can reach the shape memory transition temperature and restore its shape faster when subjected to external stimulation. The composite fiber has excellent mechanical properties and shape memory function, and can be widely used in composite fiber filling materials, textile and clothing fabrics, engineering materials, shoe materials, packaging materials, medical materials and other fields. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 are stress-strain curves of Examples 1 to 5; Figure 2 is the shape memory fixation rate of Examples 1 to 5; Figure 3 It is the shape memory recovery rate of Examples 1 to 5. DETAILED DESCRIPTION
[0021] The present invention will be further described below in conjunction with the accompanying drawings and specific embodiments.
[0022] The present invention provides a high-strength shape memory polyester composite fiber. The shape memory polyester matrix is polyethylene terephthalate-1,4-cyclohexanedimethanol (PETG) prepared by polymerization of terephthalic acid (PTA), ethylene glycol (EG) and 1,4-cyclohexanedimethanol (CHDM). The reinforcing phase uses glass fiber reinforced polyamide as a reinforcing agent to improve the strength of the shape memory polyester.
[0023] A method for preparing high-strength shape memory polyester composite fiber comprises the following steps: Step S1: The dried terephthalic acid (PTA), ethylene glycol (EG) and 1,4-cyclohexanedimethanol (CHDM) are subjected to esterification and polycondensation in a molar ratio of 1:1.2:0.8 to obtain polyethylene terephthalate-1,4-cyclohexanedimethanol (PETG) through an extruder, and the temperature of each zone of the extruder is set as follows: zone 1 240°C~250°C, zone 2 250°C~260°C, zone 3 260°C~270°C, and die head temperature 255°C~265°C. The extruded material is cooled in a water tank and pulled into a desired shape such as a filament or sheet by a traction machine.
[0024] Step S2: Use a silane coupling agent to treat the glass fiber surface to enhance the interfacial bonding between it and polyamide. The amount of silane coupling agent used is 0.5% to 2% of the mass of the glass fiber. The silane coupling agent is mixed with water or alcohol and other solvents to form a treatment liquid. The glass fiber is placed in the treatment liquid and completely immersed so that the surface of the glass fiber is fully in contact with the treatment liquid. Stir at 50°C to 80°C for 1h to 3h, and the treated glass fiber is taken out of the treatment liquid to remove the residual treatment liquid on the surface. The glass fiber is then dried, which can be done by airing naturally or drying at an appropriate temperature.
[0025] Step S3: placing the polyamide (PA) and the surface-treated glass fiber (GF) in a forced air drying oven at 60-80° C. for continuous drying for 2 h-6 h.
[0026] Step S4: adding the polyamide (PA) and glass fiber (GF) dried in step S3 into a high-speed mixer in a mass ratio of 20:1 to 7:3 and mixing them evenly at a stirring speed of 400 r / min to 1000 r / min for a stirring time of 3 min to 5 min.
[0027] Step S5: adding the mixed material processed in step S4 from the main feed port of the single screw extruder, preparing a glass fiber reinforced modified polyamide (PA) masterbatch through mixing and shearing, and setting the temperature of each zone of the extruder as follows: 225°C~235°C for zone 1, 235°C~245°C for zone 2, 245°C~255°C for zone 3, 230°C~250°C for die head, and 235°C~255°C for melt.
[0028] Step S6: The shape memory polyester chips prepared in step S1 and the glass fiber reinforced modified polyamide (PA) masterbatch prepared in step S5 are placed in a forced air drying oven at 60° C. to 100° C. for 6 h to 10 h respectively.
[0029] Step S7: adding the shape memory polyester chips (PETG) and polyamide (PA6) chips dried in step S6 into a high-speed mixer in a mass ratio of 25:1 to 7:3 and mixing them evenly at a stirring speed of 500 r / min to 1000 r / min for a stirring time of 5 min to 15 min.
[0030] Step S8: Add the material mixed evenly in step S7 from the main feeding port of the screw extruder, and obtain the shape memory polyester-based composite slices through melt blending and extrusion. The temperature of each zone of the extruder is set as follows: 240°C~250°C for zone 1, 250°C~260°C for zone 2, 260°C~270°C for zone 3, and the head temperature is 255°C~265°C.
[0031] Step S9: Add the shape memory polyester-based composite slice prepared in step S8 to the feed port of the melt spinning machine for spinning. The melt index of the composite material is 32.0g / 10min~45.0g / 10min. After drawing and cooling, a high-strength shape memory polyester composite fiber is obtained. During the melt spinning process, the temperature of each zone is set as: 210℃~220℃ for zone 1, 220℃~230℃ for zone 2, and 230℃~240℃ for zone 3. The temperature of the spinning box is controlled at 240℃~250℃. The screw extrusion pressure is 5MPa~10MPa, the spinning assembly pressure is maintained at 8MPa~12MPa, the screw speed is set to 30r / min~60r / min, and the spinning speed is 1000m / min~3000m / min.
[0032] The polyamide and glass fiber selected in the present invention are both common industrial materials with large output and relatively low price. Compared with some high-performance shape memory materials, the material cost after melt blending of modified polyamide and shape memory polyester is low, and the production cycle is short, which has a high cost performance ratio and is conducive to promotion in large-scale production and application.
[0033] The tensile strength of the shape memory polyester matrix synthesized by this method is 48.23MPa, the shape fixation rate is 89.8%, and the shape recovery rate is 85.2%. The tensile strength of the shape memory polyester composite fiber reinforced by modified polyamide is 69.5MPa, which is 44% higher than the tensile strength of the shape memory polyester matrix, the shape fixation rate is increased to 92%, and the shape recovery rate is increased to 88.2%. This is mainly because polyamide is a polymer with an amide bond (-CONH -), and there are hydrogen bond interactions between its molecular chains, which makes the polyamide itself have certain strength and toughness. When glass fiber is added to polyamide, it forms a "skeleton"-like structure in the polyamide matrix, which plays a role in supporting and carrying loads in the polyamide matrix. When the modified polyamide is used to reinforce the shape memory polyester matrix, a multiphase composite material structure is formed. In this multiphase blending system, the modified polyamide phase can provide better mechanical support for the shape memory polyester phase. Due to the presence of glass fiber, when the material is stretched by external force, the molecular chain movement of the shape memory polyester phase is restricted to a certain extent, which improves the tensile strength of the material in the initial state. At the same time, the presence of the shape memory polyester phase can also maintain the shape memory properties of the blended material.
[0034] In terms of interfacial reaction, the H atoms of the amide bond of polyamide and the O atoms of the ester bond of shape memory polyester combine to form hydrogen bonds under the action of electrostatics. Compared with simple physical adsorption, the chemically bonded interface is less likely to separate when subjected to tension. The interfacial bonding force between the two is improved under the action of hydrogen bonds, which increases the tensile strength required when the composite fiber breaks. At the same time, the glass fiber contained in the modified polyamide masterbatch is a high-strength material. During the stretching process, the glass fiber will undergo slight deformation due to the adsorption of its internal molecular structure, and finally withstand external forces, so that the composite fiber as a whole has a higher tensile strength, thereby achieving the effect of improving the mechanical properties of the composite fiber.
[0035] The shape memory polyester composite fiber prepared by this method also has good shape memory function. On the one hand, the polyamide phase can provide better support and constraint for the shape memory polyester matrix, making the material more stable during the shape recovery process; on the other hand, the addition of glass fiber improves the thermal conductivity of the material, making the temperature change of the material more uniform during heating and cooling, which is conducive to the shape memory effect. In addition, the presence of glass fiber enables the material to reach the shape memory transition temperature faster when subjected to external stimulation (such as heating), thereby accelerating the shape recovery speed. This is of great significance for some application scenarios that have strict requirements on shape recovery time, such as smart medical devices, automatic unfolding structures, etc. The present invention also limits the application scope of the shape memory polyester reinforced composite fiber, and applies it to the fields of composite fiber filling materials, textile and clothing fabrics, engineering materials, shoe materials, packaging materials, medical materials, etc.
[0036] The following will provide a clear and complete description of the technical solutions in the embodiments of the present invention in conjunction with the embodiments of the present invention. The described embodiments are only a part of the embodiments of the present invention, rather than all of the embodiments. Given the embodiments of the present invention, other embodiments obtained by those skilled in the art without creative work all fall within the scope of protection of the present invention.
[0037] A high-strength shape memory polyester composite fiber, whose raw materials include terephthalic acid (PTA), ethylene glycol (EG), 1,4-cyclohexanedimethanol (CHDM), tetrabutyl titanate, triphenyl phosphate, polyamide (PA6), and glass fiber (GF).
[0038] Embodiment 1: In this embodiment, the shape memory polyester was not subjected to enhancement and modification treatment, and was used as a control sample. The detailed preparation process thereof is as follows: Step S1: The dried terephthalic acid (PTA), ethylene glycol (EG) and 1,4-cyclohexanedimethanol (CHDM) are subjected to esterification and polycondensation in a molar ratio of 1:1.2:0.8, and the resulting polymer is extruded through an extruder. The temperature of each zone of the extruder is set as follows: 240°C for zone 1, 250°C for zone 2, 260°C for zone 3, and 255°C for die head. The extruded material is cooled in a water tank and then pulled into a desired shape such as a filament or sheet by a traction machine. Step S2: Add the shape memory polyester slices prepared in step S1 to the feed port of the melt spinning machine for spinning. The composite material melt index is 37.2g / 10min. After drawing and cooling, high-strength shape memory polyester fibers are obtained. During the melt spinning process, the temperature of each zone is set to: 210°C for zone 1, 220°C for zone 2, and 230°C for zone 3. The temperature of the spinning box is controlled at 240°C. The screw extrusion pressure is 10MPa, the spinning assembly pressure is maintained at 8MPa, the screw speed is set to 40r / min, and the spinning speed is 1500m / min to obtain shape memory polyester composite fibers.
[0039] Embodiment 2: This embodiment discloses a high-strength shape memory polyester composite fiber, and the detailed preparation process thereof is as follows: Step S1: The dried terephthalic acid (PTA), ethylene glycol (EG) and 1,4-cyclohexanedimethanol (CHDM) are subjected to esterification and polycondensation in a molar ratio of 1:1.2:0.8, and the resulting polymer is extruded through an extruder. The temperature of each zone of the extruder is set as follows: 240°C for zone 1, 250°C for zone 2, 260°C for zone 3, and 255°C for die head. The extruded material is cooled in a water tank and then pulled into a desired shape such as a filament or sheet by a traction machine. Step S2: Surface treatment of the glass fiber is performed using a silane coupling agent, wherein the amount of the silane coupling agent used is 1% of the mass of the glass fiber. The silane coupling agent and water are mixed evenly to form a treatment liquid, the glass fiber is placed in the treatment liquid and completely immersed, so that the surface of the glass fiber is fully in contact with the treatment liquid, and stirred at 60°C for 2h, the treated glass fiber is taken out from the treatment liquid, the residual treatment liquid on the surface is removed, and then the glass fiber is dried at 50°C for 4h.
[0040] Step S3: placing the polyamide (PA) and the surface-treated glass fiber (GF) in a forced air drying oven at 70° C. for 2 h.
[0041] Step S4: adding the dried polyamide (PA) and glass fiber (GF) in step S3 into a high-speed mixer at a mass ratio of 7:3 and mixing them evenly at a stirring speed of 600 r / min for 5 min.
[0042] Step S5: adding the mixed material processed in step S4 from the main feed port of the single screw extruder, preparing a glass fiber reinforced modified polyamide (PA) masterbatch through mixing and shearing, and setting the temperature of each zone of the extruder as: 225°C for zone 1, 235°C for zone 2, 245°C for zone 3, 230°C for die head, and 235°C for melt.
[0043] Step S6: The shape memory polyester chips prepared in step S1 and the glass fiber reinforced modified polyamide (PA) masterbatch prepared in step S5 are placed in a forced air drying oven at 80° C. for 7 hours.
[0044] Step S7: the shape memory polyester chips (PETG) and polyamide (PA6) chips dried in step S6 are added into a high-speed mixer at a mass ratio of 25:1 and mixed evenly at a stirring speed of 600 r / min for 10 min.
[0045] Step S8: Add the material mixed evenly in step S7 from the main feeding port of the screw extruder, and obtain shape memory polyester-based composite chips through melt blending and extrusion. The temperature of each zone of the extruder is set as follows: 240°C for zone 1, 250°C for zone 2, 260°C for zone 3, and 255°C for the die head.
[0046] Step S9: Add the shape memory polyester-based composite slice prepared in step S8 to the feed port of the melt spinning machine for spinning. The composite material melt index is 35g / 10min. After drawing and cooling, a high-strength shape memory polyester composite fiber is obtained. During the melt spinning process, the temperature of each zone is set to: 210°C in zone 1, 220°C in zone 2, and 230°C in zone 3. The temperature of the spinning box is controlled at 240°C. The screw extrusion pressure is 10MPa, the spinning assembly pressure is maintained at 8MPa, the screw speed is set to 40r / min, and the spinning speed is 1500m / min to obtain a high-strength shape memory polyester composite fiber.
[0047] Embodiment 3: This embodiment discloses a high-strength shape memory polyester composite fiber, and the detailed preparation process thereof is as follows: Step S1: The dried terephthalic acid (PTA), ethylene glycol (EG) and 1,4-cyclohexanedimethanol (CHDM) are subjected to esterification and polycondensation in a molar ratio of 1:1.2:0.8, and the resulting polymer is extruded through an extruder. The temperature of each zone of the extruder is set as follows: 240°C for zone 1, 250°C for zone 2, 260°C for zone 3, and 255°C for die head. The extruded material is cooled in a water tank and then pulled into a desired shape such as a filament or sheet by a traction machine. Step S2: Surface treatment of the glass fiber is performed using a silane coupling agent, wherein the amount of the silane coupling agent used is 1% of the mass of the glass fiber. The silane coupling agent and water are mixed evenly to form a treatment liquid, the glass fiber is placed in the treatment liquid and completely immersed, so that the surface of the glass fiber is fully in contact with the treatment liquid, and stirred at 60°C for 2h, the treated glass fiber is taken out from the treatment liquid, the residual treatment liquid on the surface is removed, and then the glass fiber is dried at 50°C for 4h.
[0048] Step S3: placing the polyamide (PA) and the surface-treated glass fiber (GF) in a forced air drying oven at 70° C. for 2 h.
[0049] Step S4: adding the dried polyamide (PA) and glass fiber (GF) in step S3 into a high-speed mixer at a mass ratio of 7:3 and mixing them evenly at a stirring speed of 600 r / min for 5 min.
[0050] Step S5: adding the mixed material processed in step S4 from the main feed port of the single screw extruder, preparing a glass fiber reinforced modified polyamide (PA) masterbatch through mixing and shearing, and setting the temperature of each zone of the extruder as: 225°C for zone 1, 235°C for zone 2, 245°C for zone 3, 230°C for die head, and 235°C for melt.
[0051] Step S6: The shape memory polyester chips prepared in step S1 and the glass fiber reinforced modified polyamide (PA) masterbatch prepared in step S5 are placed in a forced air drying oven at 80° C. for 7 hours.
[0052] Step S7: the shape memory polyester chips (PETG) and polyamide (PA6) chips after drying in step S6 are added into a high-speed mixer at a mass ratio of 16:1 and mixed evenly at a stirring speed of 600 r / min for 10 min.
[0053] Step S8: Add the material mixed evenly in step S7 from the main feeding port of the screw extruder, and obtain shape memory polyester-based composite chips through melt blending and extrusion. The temperature of each zone of the extruder is set as follows: 240°C for zone 1, 250°C for zone 2, 260°C for zone 3, and 255°C for the die head.
[0054] Step S9: Add the shape memory polyester-based composite slice prepared in step S8 to the feed port of the melt spinning machine for spinning. The melt index of the composite material is 36.8g / 10min. After drawing and cooling, a high-strength shape memory polyester composite fiber is obtained. During the melt spinning process, the temperature of each zone is set to: 210°C for zone 1, 220°C for zone 2, and 230°C for zone 3. The temperature of the spinning box is controlled at 240°C. The screw extrusion pressure is 10MPa, the spinning assembly pressure is maintained at 8MPa, the screw speed is set to 40r / min, and the spinning speed is 1500m / min to obtain a high-strength shape memory polyester composite fiber.
[0055] Embodiment 4: This embodiment discloses a high-strength shape memory polyester composite fiber, and the detailed preparation process thereof is as follows: Step S1: The dried terephthalic acid (PTA), ethylene glycol (EG) and 1,4-cyclohexanedimethanol (CHDM) are subjected to esterification and polycondensation in a molar ratio of 1:1.2:0.8, and the resulting polymer is extruded through an extruder. The temperature of each zone of the extruder is set as follows: 240°C for zone 1, 250°C for zone 2, 260°C for zone 3, and 255°C for die head. The extruded material is cooled in a water tank and then pulled into a desired shape such as a filament or sheet by a traction machine. Step S2: Surface treatment of the glass fiber is performed using a silane coupling agent, wherein the amount of the silane coupling agent used is 1% of the mass of the glass fiber. The silane coupling agent and water are mixed evenly to form a treatment liquid, the glass fiber is placed in the treatment liquid and completely immersed, so that the surface of the glass fiber is fully in contact with the treatment liquid, and stirred at 60°C for 2h, the treated glass fiber is taken out from the treatment liquid, the residual treatment liquid on the surface is removed, and then the glass fiber is dried at 50°C for 4h.
[0056] Step S3: placing the polyamide (PA) and the surface-treated glass fiber (GF) in a forced air drying oven at 70° C. for 2 h.
[0057] Step S4: adding the dried polyamide (PA) and glass fiber (GF) in step S3 into a high-speed mixer at a mass ratio of 7:3 and mixing them evenly at a stirring speed of 600 r / min for 5 min.
[0058] Step S5: adding the mixed material processed in step S4 from the main feed port of the single screw extruder, preparing a glass fiber reinforced modified polyamide (PA) masterbatch through mixing and shearing, and setting the temperature of each zone of the extruder as: 225°C for zone 1, 235°C for zone 2, 245°C for zone 3, 230°C for die head, and 235°C for melt.
[0059] Step S6: The shape memory polyester chips prepared in step S1 and the glass fiber reinforced modified polyamide (PA) masterbatch prepared in step S5 are placed in a forced air drying oven at 80° C. for 7 hours.
[0060] Step S7: adding the shape memory polyester chips (PETG) and polyamide (PA6) chips dried in step S6 into a high-speed mixer at a mass ratio of 12:1 and mixing them evenly at a stirring speed of 600 r / min for 10 min.
[0061] Step S8: Add the material mixed evenly in step S7 from the main feeding port of the screw extruder, and obtain shape memory polyester-based composite chips through melt blending and extrusion. The temperature of each zone of the extruder is set as follows: 240°C for zone 1, 250°C for zone 2, 260°C for zone 3, and 255°C for the die head.
[0062] Step S9: Add the shape memory polyester-based composite slice prepared in step S8 to the feed port of the melt spinning machine for spinning. The melt index of the composite material is 38.2g / 10min. After drawing and cooling, a high-strength shape memory polyester composite fiber is obtained. During the melt spinning process, the temperature of each zone is set to: 210°C for zone 1, 220°C for zone 2, and 230°C for zone 3. The temperature of the spinning box is controlled at 240°C. The screw extrusion pressure is 10MPa, the spinning assembly pressure is maintained at 8MPa, the screw speed is set to 40r / min, and the spinning speed is 1500m / min to obtain a high-strength shape memory polyester composite fiber.
[0063] Embodiment 5: This embodiment discloses a high-strength shape memory polyester composite fiber, and the detailed preparation process thereof is as follows: Step S1: The dried terephthalic acid (PTA), ethylene glycol (EG) and 1,4-cyclohexanedimethanol (CHDM) are subjected to esterification and polycondensation in a molar ratio of 1:1.2:0.8, and the resulting polymer is extruded through an extruder. The temperature of each zone of the extruder is set as follows: 240°C for zone 1, 250°C for zone 2, 260°C for zone 3, and 255°C for die head. The extruded material is cooled in a water tank and then pulled into a desired shape such as a filament or sheet by a traction machine. Step S2: Surface treatment of the glass fiber is performed using a silane coupling agent, wherein the amount of the silane coupling agent used is 1% of the mass of the glass fiber. The silane coupling agent and water are mixed evenly to form a treatment liquid, the glass fiber is placed in the treatment liquid and completely immersed, so that the surface of the glass fiber is fully in contact with the treatment liquid, and stirred at 60°C for 2h, the treated glass fiber is taken out from the treatment liquid, the residual treatment liquid on the surface is removed, and then the glass fiber is dried at 50°C for 4h.
[0064] Step S3: placing the polyamide (PA) and the surface-treated glass fiber (GF) in a forced air drying oven at 70° C. for 2 h.
[0065] Step S4: adding the dried polyamide (PA) and glass fiber (GF) in step S3 into a high-speed mixer at a mass ratio of 7:3 and mixing them evenly at a stirring speed of 600 r / min for 5 min.
[0066] Step S5: adding the mixed material processed in step S4 from the main feed port of the single screw extruder, preparing a glass fiber reinforced modified polyamide (PA) masterbatch through mixing and shearing, and setting the temperature of each zone of the extruder as: 225°C for zone 1, 235°C for zone 2, 245°C for zone 3, 230°C for die head, and 235°C for melt.
[0067] Step S6: The shape memory polyester chips prepared in step S1 and the glass fiber reinforced modified polyamide (PA) masterbatch prepared in step S5 are placed in a forced air drying oven at 80° C. for 7 hours.
[0068] Step S7: the shape memory polyester chips (PETG) and polyamide (PA6) chips dried in step S6 are added into a high-speed mixer at a mass ratio of 9:1 and mixed evenly at a stirring speed of 600 r / min for 10 min.
[0069] Step S8: Add the material mixed evenly in step S7 from the main feeding port of the screw extruder, and obtain shape memory polyester-based composite chips through melt blending and extrusion. The temperature of each zone of the extruder is set as follows: 240°C for zone 1, 250°C for zone 2, 260°C for zone 3, and 255°C for the die head.
[0070] Step S9: Add the shape memory polyester-based composite slice prepared in step S8 to the feed port of the melt spinning machine for spinning. The melt index of the composite material is 37.5g / 10min. After drawing and cooling, a high-strength shape memory polyester composite fiber is obtained. During the melt spinning process, the temperature of each zone is set as: 210°C in zone 1, 220°C in zone 2, and 230°C in zone 3. The temperature of the spinning box is controlled at 240°C. The screw extrusion pressure is 10MPa, the spinning assembly pressure is maintained at 8MPa, the screw speed is set to 40r / min, and the spinning speed is 1500m / min to obtain a high-strength shape memory polyester composite fiber.
[0071] Embodiment 6: Step S1: The dried terephthalic acid (PTA), ethylene glycol (EG) and 1,4-cyclohexanedimethanol (CHDM) are subjected to esterification and polycondensation in a molar ratio of 1:1.2:0.8, and the resulting polymer is extruded through an extruder. The temperature of each zone of the extruder is set as follows: 240°C for zone 1, 250°C for zone 2, 260°C for zone 3, and 255°C for die head. The extruded material is cooled in a water tank and then pulled into a desired shape such as a filament or sheet by a traction machine. Step S2: Surface treatment of the glass fiber is performed using a silane coupling agent, wherein the amount of the silane coupling agent used is 0.5% of the mass of the glass fiber. The silane coupling agent and water are mixed evenly to form a treatment liquid, the glass fiber is placed in the treatment liquid and completely immersed, so that the surface of the glass fiber is fully in contact with the treatment liquid, and stirred at 60°C for 2h, the treated glass fiber is taken out from the treatment liquid, the residual treatment liquid on the surface is removed, and then the glass fiber is dried at 50°C for 4h.
[0072] Step S3: placing the polyamide (PA) and the surface-treated glass fiber (GF) in a forced air drying oven at 70° C. for 2 h.
[0073] Step S4: Add the dried polyamide (PA) and glass fiber (GF) in step S3 into a high-speed mixer at a mass ratio of 20:1 and mix them evenly at a stirring speed of 600 r / min for 5 min.
[0074] Step S5: adding the mixed material processed in step S4 from the main feed port of the single screw extruder, preparing a glass fiber reinforced modified polyamide (PA) masterbatch through mixing and shearing, and setting the temperature of each zone of the extruder as: 225°C for zone 1, 235°C for zone 2, 245°C for zone 3, 230°C for die head, and 235°C for melt.
[0075] Step S6: The shape memory polyester chips prepared in step S1 and the glass fiber reinforced modified polyamide (PA) masterbatch prepared in step S5 are placed in a forced air drying oven at 80° C. for 7 hours.
[0076] Step S7: the shape memory polyester chips (PETG) and polyamide (PA6) chips dried in step S6 are added into a high-speed mixer at a mass ratio of 9:1 and mixed evenly at a stirring speed of 600 r / min for 10 min.
[0077] Step S8: Add the material mixed evenly in step S7 from the main feeding port of the screw extruder, and obtain shape memory polyester-based composite chips through melt blending and extrusion. The temperature of each zone of the extruder is set as follows: 240°C for zone 1, 250°C for zone 2, 260°C for zone 3, and 255°C for the die head.
[0078] Step S9: Add the shape memory polyester-based composite slice prepared in step S8 to the feed port of the melt spinning machine for spinning. The melt index of the composite material is 32.0g / 10min. After drawing and cooling, a high-strength shape memory polyester composite fiber is obtained. During the melt spinning process, the temperature of each zone is set to: 210°C in zone 1, 220°C in zone 2, and 230°C in zone 3. The temperature of the spinning box is controlled at 240°C. The screw extrusion pressure is 10MPa, the spinning assembly pressure is maintained at 8MPa, the screw speed is set to 40r / min, and the spinning speed is 1500m / min to obtain a high-strength shape memory polyester composite fiber.
[0079] Embodiment 7: Step S1: The dried terephthalic acid (PTA), ethylene glycol (EG) and 1,4-cyclohexanedimethanol (CHDM) are subjected to esterification and polycondensation in a molar ratio of 1:1.2:0.8, and the resulting polymer is extruded through an extruder. The temperature of each zone of the extruder is set to: 245°C for zone 1, 255°C for zone 2, 265°C for zone 3, and 258°C for die head. The extruded material is cooled in a water tank and then pulled into a desired shape such as a filament or sheet by a traction machine. Step S2: Surface treatment of the glass fiber is performed using a silane coupling agent, wherein the amount of the silane coupling agent used is 1.5% of the mass of the glass fiber. The silane coupling agent and water are mixed evenly to form a treatment liquid, the glass fiber is placed in the treatment liquid and completely immersed, so that the surface of the glass fiber is fully in contact with the treatment liquid, and stirred at 50°C for 3 hours, the treated glass fiber is taken out from the treatment liquid, the residual treatment liquid on the surface is removed, and then the glass fiber is dried at 50°C for 4 hours.
[0080] Step S3: placing the polyamide (PA) and the surface-treated glass fiber (GF) in a forced air drying oven at 60° C. for 6 hours.
[0081] Step S4: adding the polyamide (PA) and glass fiber (GF) dried in step S3 into a high-speed mixer at a mass ratio of 10:3 and mixing them evenly at a stirring speed of 400 r / min for 4 min.
[0082] Step S5: adding the mixed material processed in step S4 from the main feeding port of the single screw extruder, preparing a glass fiber reinforced modified polyamide (PA) masterbatch through mixing and shearing, and setting the temperature of each zone of the extruder as: 230°C for zone 1, 240°C for zone 2, 248°C for zone 3, 240°C for die head, and 250°C for melt temperature.
[0083] Step S6: The shape memory polyester chips prepared in step S1 and the glass fiber reinforced modified polyamide (PA) masterbatch prepared in step S5 are placed in a forced air drying oven at 100° C. for 6 hours.
[0084] Step S7: adding the shape memory polyester chips (PETG) and polyamide (PA6) chips dried in step S6 into a high-speed mixer at a mass ratio of 9:1 and mixing them evenly at a stirring speed of 1000 r / min for 5 min.
[0085] Step S8: Add the material mixed evenly in step S7 from the main feeding port of the screw extruder, and obtain shape memory polyester-based composite chips through melt blending and extrusion. The temperature of each zone of the extruder is set as follows: 245°C for zone 1, 255°C for zone 2, 265°C for zone 3, and 255°C for die head.
[0086] Step S9: Add the shape memory polyester-based composite slice prepared in step S8 to the feed port of the melt spinning machine for spinning. The composite material melt index is 38.1g / 10min. After drawing and cooling, a high-strength shape memory polyester composite fiber is obtained. During the melt spinning process, the temperature of each zone is set as: 215°C in zone 1, 2205°C in zone 2, and 235°C in zone 3. The temperature of the spinning box is controlled at 245°C. The screw extrusion pressure is 8MPa, the spinning assembly pressure is maintained at 10MPa, the screw speed is set to 30r / min, and the spinning speed is 3000m / min to obtain a high-strength shape memory polyester composite fiber.
[0087] Embodiment 8: Step S1: The dried terephthalic acid (PTA), ethylene glycol (EG) and 1,4-cyclohexanedimethanol (CHDM) are subjected to esterification and polycondensation in a molar ratio of 1:1.2:0.8, and the resulting polymer is extruded through an extruder. The temperature of each zone of the extruder is set to: 250°C for zone 1, 260°C for zone 2, 270°C for zone 3, and 265°C for die head. The extruded material is cooled in a water tank and then pulled into a desired shape such as a filament or sheet by a traction machine. Step S2: Surface treatment of the glass fiber is performed using a silane coupling agent, wherein the amount of the silane coupling agent used is 2% of the mass of the glass fiber. The silane coupling agent and water are mixed evenly to form a treatment liquid, the glass fiber is placed in the treatment liquid and completely immersed, so that the surface of the glass fiber is fully in contact with the treatment liquid, and stirred at 80°C for 1 hour, the treated glass fiber is taken out from the treatment liquid, the residual treatment liquid on the surface is removed, and then the glass fiber is dried at 50°C for 4 hours.
[0088] Step S3: placing the polyamide (PA) and the surface-treated glass fiber (GF) in a forced air drying oven at 80° C. for 3 hours.
[0089] Step S4: Add the dried polyamide (PA) and glass fiber (GF) in step S3 into a high-speed mixer at a mass ratio of 7:3 and mix them evenly at a stirring speed of 1000 r / min for 3 min.
[0090] Step S5: adding the mixed material processed in step S4 from the main feed port of the single screw extruder, preparing a glass fiber reinforced modified polyamide (PA) masterbatch through mixing and shearing, and setting the temperature of each zone of the extruder as: 225°C for zone 1, 235°C for zone 2, 245°C for zone 3, 230°C for die head, and 235°C for melt.
[0091] Step S6: The shape memory polyester chips prepared in step S1 and the glass fiber reinforced modified polyamide (PA) masterbatch prepared in step S5 are placed in a forced air drying oven at 60° C. for 10 hours.
[0092] Step S7: the shape memory polyester chips (PETG) and polyamide (PA6) chips dried in step S6 are added into a high-speed mixer at a mass ratio of 9:1 and mixed evenly at a stirring speed of 500 r / min for 15 min.
[0093] Step S8: Add the material mixed evenly in step S7 from the main feeding port of the screw extruder, and obtain shape memory polyester-based composite chips through melt blending and extrusion. The temperature of each zone of the extruder is set as follows: 250°C for zone 1, 260°C for zone 2, 270°C for zone 3, and 265°C for the head temperature.
[0094] Step S9: Add the shape memory polyester-based composite slice prepared in step S8 to the feed port of the melt spinning machine for spinning. The composite material melt index is 45.0g / 10min. After drawing and cooling, a high-strength shape memory polyester composite fiber is obtained. During the melt spinning process, the temperature of each zone is set as: 220°C for zone 1, 230°C for zone 2, and 240°C for zone 3. The temperature of the spinning box is controlled at 240°C. The screw extrusion pressure is 5MPa, the spinning assembly pressure is maintained at 12MPa, the screw speed is set to 30r / min, and the spinning speed is 1000m / min to obtain a high-strength shape memory polyester composite fiber.
[0095] The tensile strength of the composite fibers of Examples 1 to 5 was measured. Figure 1 As shown. Figure 1 It can be seen from the test results that the tensile strength of Example 1 is 48.23 MPa, the tensile strength of Example 2 is 53.58 MPa, the tensile strength of Example 3 is 60 MPa, the tensile strength of Example 4 is 65.16 MPa, and the tensile strength of Example 5 is 69.5 MPa, which are all significantly improved on the basis of the tensile strength of the raw materials.
[0096] Figure 2 The shape fixation rate of high-strength shape memory polyester composite fiber, Figure 3 is the shape recovery rate of high-strength shape memory polyester composite fiber. It can be seen that the shape memory performance of the composite fiber is significantly improved compared with pure PETG fiber; with the increase of PA6 content, the shape fixation rate shows a trend of first increasing and then decreasing. When the PA6 content is 8%, the shape fixation rate reaches a maximum of 92%, and the shape recovery rate shows an increasing trend. When the PA6 content is 10%, the shape recovery rate reaches a maximum of 88.9%; among them, PA6 10wt% has the best shape memory performance, with a shape fixation rate and shape recovery rate of 91.7% and 88.9% respectively, which are 2.1% and 4.3% higher than the shape memory polyester matrix.
[0097] The following table shows the test results of tensile strength, shape fixation rate and shape recovery rate of shape memory polyester composite fibers in Examples 6 to 7. It can be seen that the strength of the modified shape memory polyester composite fibers is improved, and the shape fixation rate and recovery rate are both high, and the fibers have good shape memory function.
[0098]
[0099] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A modified polyamide-reinforced shape memory polyester, characterized in that: include: Shape memory polyester matrix: polyethylene terephthalate-1,4-cyclohexanedimethanol ester; Reinforcement phase: glass fiber modified polyamide; Among them, the mass ratio of shape memory polyester matrix to reinforcement phase is 25:1~7:
3.
2. The modified polyamide-reinforced shape memory polyester according to claim 1, characterized in that: The preparation of the shape memory polyester matrix is as follows: Terephthalic acid, ethylene glycol and 1,4-cyclohexanedimethanol are mixed in a molar ratio of 1:1.2:0.8 to obtain a mixture; The mixed material is extruded through an extruder, and the temperature of each zone of the extruder is set as follows: 240°C-250°C for zone 1, 250°C-260°C for zone 2, 260°C-270°C for zone 3, and a die head temperature of 255°C-265°C to obtain polyethylene terephthalate-1,4-cyclohexanedimethanol ester.
3. The modified polyamide-reinforced shape memory polyester according to claim 1, characterized in that: The preparation method of glass fiber modified polyamide is as follows: The glass fiber is immersed in a silane coupling agent treatment liquid to obtain a pretreated glass fiber; The polyamide and the pretreated glass fiber are mixed and then extruded through an extruder to obtain the glass fiber modified polyamide.
4. The modified polyamide-reinforced shape memory polyester according to claim 3, characterized in that: In the step of immersing the glass fiber in a silane coupling agent treatment solution to obtain the pretreated glass fiber, specifically: The amount of the silane coupling agent is 0.5% to 2% of the mass of the glass fiber; The glass fiber is completely immersed in the silane coupling agent treatment solution and stirred at 50°C to 80°C for 1 to 3 hours. The glass fiber is taken out and dried to obtain the pretreated glass fiber.
5. The modified polyamide-reinforced shape memory polyester according to claim 3, characterized in that: In the step of mixing polyamide and pretreated glass fiber and then extruding through an extruder to obtain glass fiber modified polyamide, specifically: The polyamide and the glass fiber are mixed in a mass ratio of 20:1 to 7:3, stirred for 3 to 5 minutes at a stirring speed of 400 r / min to 1000 r / min to obtain a mixed material, and the mixed material is added to an extruder.
6. The modified polyamide-reinforced shape memory polyester according to claim 3, characterized in that: In the step of mixing polyamide and pretreated glass fiber and then extruding through an extruder to obtain glass fiber modified polyamide, specifically: The temperature settings of each zone of the extruder are: zone 1 225℃~235℃, zone 2 235℃~245℃, zone 3 245℃~255℃, head temperature 230℃~250℃, and melt temperature 235℃~255℃.
7. The modified polyamide-reinforced shape memory polyester according to claim 1, characterized in that: Polyethylene terephthalate-1,4-cyclohexanedimethanol ester and glass fiber modified polyamide are mixed in a mass ratio of 25:1-7:3, stirred for 5-15 minutes at 500-1000 r / min, and extruded by an extruder; the temperature of each zone of the extruder is set as follows: 240-250°C for zone 1, 250-260°C for zone 2, 260-270°C for zone 3, and the die head temperature is 255-265°C.
8. A high-strength shape memory polyester composite fiber, characterized in that: The modified polyamide-reinforced shape memory polyester according to any one of claims 1 to 7 is used for melt spinning, wherein the melt index of the modified polyamide-reinforced shape memory polyester is 32.0 g / 10 min to 45.0 g / 10 min.
9. The high-strength shape memory polyester composite fiber according to claim 8, characterized in that: During melt spinning, the temperature of each zone is set as: 210℃~220℃ for zone 1, 220℃~230℃ for zone 2, and 230℃~240℃ for zone 3; the temperature of the spinning box is controlled at 240℃~250℃; the screw extrusion pressure is 5MPa~10MPa, the spinning assembly pressure is 8MPa~12MPa, the screw speed is 30r / min~60r / min, and the spinning speed is 1000m / min~3000m / min.
10. Use of the high-strength shape memory polyester composite fiber according to claim 8 or 9 in composite fiber filling materials, textile and clothing fabrics, engineering materials, shoe materials, packaging materials or medical materials.